KAVA CONSUMPTION AND FAMILY VIOLENCE - Ofanoa, Malakai; Ofanoa, Samuela (Advances in Social Sciences Research Journal, 2021)
Kava drinking has become an intrinsic part of Tongan culture. It involves regular participation and high consumption of kava drink in kava clubs and other kava venues in Tonga and New Zealand. However, mounting evidence has indicated that the reasons for, and perceived effects of kava consumption are yet to be fully understood (Nosa and Ofanoa, 2009, Ofanoa, 2010). A qualitative study to explore the issues related with Tongan men abusing kava consumption was conducted in Tonga and Auckland, New Zealand (Ofanoa, 2010). The study used culturally safe, Pacific qualitative research approaches of Kakala (Thaman, 1997) and Talanga (Ofanoa, 2010) to obtain information related to the issue. There were focus group interviews conducted with a convenience sample of 104 Tongan men across 5 kava clubs each in Tonga and Auckland, New Zealand. The analysis of the focus group interviews in both places involved a general inductive approach. The findings reported that kava use is socially sanctioned and easily accessible in both countries. Further, kava presents concerning health and social issues. It increases poor family relationships that leads to family violence. Usually the family violence happens after kava sessions. The Kava men sleep long hours; they spent a lot of their family income in Kava sessions and makes many excuses. Moreover, kava men are usually very lazy to work, and slow to recover in the next day. Hence, the poor wives usually shoulder everything in the family. In many instances, some of them behave violently and aggressively. When such practices happen consistently, family violence starts, and many husbands physically abuse their wives. Evidently, one end up in the hospital with serious injuries or both husband and wife appear in court. The study concludes that Tongan men in both countries cannot continue to hide the truth that their abusive consumption of kava contributes to family violence. Hence, there is a tremendous need for urgent actions to prevent and minimize this practice. Further, since addressing the issue is sensitive and complex, a call for multi-sectoral and multi-disciplinary effort with the Tongan society in both Tonga and New Zealand is required to minimize the risks and optimize the benefits of kava use.